Study on Potential Toxic Mechanism of Chrysophanol Binding DNA by Saturation Value Binding DNA - Xiao-Mei, Yang; Jun-Sheng, Li; Guo-Xia, Huang; Qi-Qian, Li; Liu-Juan, Yan (Asian Journal of Chemistry, 2011)
In this study, the interaction of chrysophanol and DNA is reported to reveal the toxic mechanism of chrysophanol by the resonance light scattering spectrum. Meanwhile, the saturation value binding DNA is calculated from the resonance light scattering results to evaluate the ability of intercalating into DNA and the potential toxicity of chrysophanol. As the resonance light scattering results of chrysophanol interacting with DNA is very similar to these of ethidium bromide, adriamycin and mitoxantrone, it is believed that the chrysophanol can also intercalate into the base pairs of double-helical DNA in a similar DNA intercalator way. The saturation value of the binding DNA of chrysophanol is much lower than those of mitoxantrone, adriamycin and ethidium bromide. Therefore, it can be speculated that chrysophanol shows a weak capacity of intercalating into DNA. The saturation value changed with environmental factors, such as amino acids, sodium chloride, glucose and pH. The saturation value binding DNA can be evaluated the potential toxicity of anthraquinone derivatives and the toxic effects in terms of external factors and conditions.